Implikasi Yuridis Riwayat tentang Kesalahan Penulisan dalam Mushaf Usmani - Ahmad Rajafi (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2017)
The history of writing error in the Qur'an derived from Aisha and justified by Khalifa Uthman bin Affan received a different responses among Islamic researchers, both from the strictly rejecting that history of writing (riwayat) until to those who accepted the existence the riwayat but with different